Implementation of Internet of Things in the Development of Sign Language Translator Gloves Using Flex Sensors - Sihombing, Gracia Napare; Hamzah, Afif; Purba, Julio Aldrin; Hutahaean, Harvei Desmon (Bahasa Indonesia, 2023)
This research focuses on the development of gloves utilising flex sensors that translate hand gestures into sign language. Designed specifically for a person with a disability to communicate with others who do not understand sign language. The prototype method is used in this research with the stages of user identification, code generation and implementation, prototype testing and evaluation. The test results show that the readability rate is between 20% to 90% using SIBI gestures, the readability rate is high in some specific gestures. Integrating gloves with flex sensors creates a communication tool that is comfortable, easy and efficient to use.